Anti-Inflammatory Effects of Berberine Hydrochloride in an LPS-Induced Murine Model of Mastitis. (15th April 2018) - Wang, Xichun; Feng, Shibin; Ding, Nana; He, Yanting; Li, Cheng; Li, Manman; Ding, Xuedong; Ding, Hongyan; Li, Jinchun; Wu, Jinjie; Li, Yu
Abstract : Berberine hydrochloride is an isoquinoline type alkaloid extracted from Berberidaceae, Rutaceae, and other plants. Previous reports have shown that berberine hydrochloride has anti-inflammatory properties. However, the underlying molecular mechanisms remain unclear. In this study, a lipopolysaccharide- (LPS-) induced murine model of mastitis was established to explore the anti-inflammatory action of berberine hydrochloride. Sixty mice that had been lactating for 5–7 days were randomly divided into six groups, including control, LPS, three berberine hydrochloride treatment groups (5, 10, and 20 mg/kg), and a dexamethasone (DEX) (5 mg/kg) group. Berberine hydrochloride was administered intraperitoneally 1 h before and 12 h after LPS-induced mastitis, and all mice were sacrificed 24 h after LPS induction. The pathological and histopathological changes of the mammary glands were observed. The concentrations and mRNA expressions of TNF- α, IL-1 β, and IL-6 were measured by ELISA and qRT-PCR. The activation of TLR4 and NF- κ B signaling pathways was analyzed by Western blot. Results indicated that berberine hydrochloride significantly attenuated neutrophil infiltration and dose-dependently decreased the secretion and mRNA expressions of TNF- α, IL-1 β, and IL-6 within a certain range. Furthermore, berberine hydrochloride suppressed LPS-induced TLR4 and NF- κ B p65 activation and the phosphorylation of I- κ B. Berberine hydrochloride can provide mice robust protection from LPS-induced mastitis, potentially via the TLR4 and NF- κ B pathway.